Determinants of Flood Disaster Households’ Vulnerability in Nepal - Bista, Raghu Bir (Economic Journal of Development Issues, 2019)
Almost all extreme socio economic vulnerabilities relate to natural disasters and its economic loss at household level, along with socio economic characteristics of household. This relationship creates great curiosity estimating determinants and levels of vulnerability at micro level for policy understanding for minimizing household vulnerability. This paper measures empirically the determinants of vulnerability of natural disasters at household level based on primary data sets collected from household survey in Sot Khola water basin by using multiple econometric models. The descriptive analysis shows a huge loss with a worth 13,344,000 Rupees including crops, assets and physical infrastructure. Despite its small worth, life was worst due to loss of house, crops, clean drinking water, electricity, documents, foods, communication, displacement etc. Furthermore, the result of the model shows rural orthodox society having indigenous knowledge and skill, conservative agrarian family, traditional labor force, primitive technology etc. Loss and income of household have positive relationship but labor, early warning and knowledge of disasters have negative relationship. Knowledge of disasters have made household resilient to reduce economic loss and then household vulnerability. Households in the geography of Gadhi and Lekhagaon are more resilient than of Kunathari. Therefore, climate resilience is urgent issue to minimize household vulnerability for household income and welfare.